Measure the symptoms related to Pre-Menstrual Syndrome among married and unmarried females during their reproductive life span. - Sonya Arshad; Muhammad Nisar; Syeda Hiba Hashmi (International Journal of Endorsing Health Science Research, 2017)
Objective: The study was aimed to estimate premenstrual syndrome and its consequent symptoms in married and unmarried females during menstrual phase, pre-ovulatory phase and post-ovulatory phase. Methodology: A cross sectional survey based study has been conducted in young females of 25-35 age groups. Participants were divided into two groups. Group A were with PMS and group B were healthy subjects. The evaluation of manifestations in all three phases was gathered by using PRISM calendar. The data was collected and stored and analyzed by applying Chi-square test by using SPSS v.22.0. Results: The result revealed that the severity was different among unmarried (55%) and married (50%) in all three phases of Menstrual cycle. Unmarried female shows their symptoms 54.5% in menstrual phase, 27.3%in post ovulatory phase and 18.2% in pre-ovulatory phase, while married females express 50%, 30%, and 20.0% respectively in all the three phases. The significant (p<0.05) result were recorded in menstrual phase by showing back pain, anxiety, breast pain, headache, depression, nausea, abdominal cramps, irritability and swelling in both married and unmarried women. While Diarrhea and vomiting found on-significant (p>0.05). Constipation was additional significant factor present in married females. Discussion: The present study among unmarried females and married females revealed that premenstrual syndrome (PMS) differs in each of three groups. Women of reproductive age either married or unmarried showing significant symptoms of PMS, however different phases have different percentage among these two groups. Conclusion: According to our results, we concluded that in unmarried and married females, PMS were found frequently during menstrual phase and remaining two phases has no prevailing clinical manifestation.